Continuous molecular adsorbent recirculating system treatment in 69 patients listed for liver transplantation. (September 2015) - Olin, Per; Hausken, John; Foss, Aksel; Karlsen, Tom Hemming; Melum, Espen; Haugaa, Håkon
Abstract Objective. The molecular adsorbent recirculating system (MARS) is used to purify blood from albumin-bound toxins in patients with liver failure. However, the application of MARS has not demonstrated improved survival in randomized clinical trials and the clinical utility has not been finally established. In our department, the use of MARS is now restricted to the most critically ill patients with acute or acute on chronic liver failure. Material and methods. Since 2005, we have treated 69 patients (30 males/39 females with median age of 49 years ranging from 1 months to 70 years) listed for liver transplantation (LT) with MARS. Median model of end-stage liver disease score in patients older than 12 years of age (n = 56) was 33 (interquartile range 26–39). The flow rate was 35–40 mL/kg/h and treatment kits were changed every 8–12 h. The patients were treated for a median of 27 h (range 1–144 h). Results. Fifty-six patients (81%) were transplanted. Nine died before they could be transplanted, and four patients recovered without transplantation. Forty-six (82%) of the transplanted patients were alive 30 days after transplantation. Ammonium decreased modestly from a median of 148 to 124 µM (p = 0.03) during MARS treatment. We detected worsening of coagulopathy with significant decreases in platelet count and fibrinogen concentrations, and increase in International Normalized Ratio. Phosphate and magnesium decreased significantly during MARS treatment. Conclusion. Continuous MARS therapy may bridge liver failure patients to LT under close observation and treatment of coagulopathy and electrolyte disturbances.